A Collaborative Study Designed to Establish the 4th International Standard for Heparin - Thomas, D P; Curtis, A D; Barrowcliffe, T W (Thrombosis and Haemostasis, 1984)
An international collaborative study, in which 22 laboratories participated, was carried out to establish a replacement for the International Standard for Heparin. A total of 248 assays were analyzed, including APTT, thrombin inhibition and anti-Xa assays, as well as pharmacopoeial assays. Overall, there was less than 5% difference in the mean potency estimates of the candidate preparations, by all assay methods. The freeze-dried preparation 82/502 demonstrated the closest parallelism by bioassay to the existing standard and was established by WHO as the 4th International Standard for Heparin, with an assigned unitage of 1780 i.u. per ampoule.
Keywords: Heparin; Standard